Anticorpos para Borrelia burgdorferi em indivíduos que trabalham com animais silvestres - Corradi, D. A.; Carvalho, V. M.; Coutinho, S. D. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2006)
The occurrence of serum antibodies to Borrelia burgdorferi in professionals in close contact with wild animals was determined. Seventy eight technicians workers coming from two São Paulo public institutions housing wild animals had their blood collected (serum samples). All samples were submitted to ELISA for IgM and IgG antibodies against Borrelia burgdorferi. The results showed five positive (6.4%), two suspect (2.6%) and 71 negatives (91%) samples. Based on positive results it is concluded that the infection level is higher to that detected in the general population and similar to values of endemic areas, concluding that this assessed population could be considered at risk for Lyme disease.
Antibodies specific to Borrelia burgdorferi in wild animal workers
Keywords: Borrelia burgdorferi; wild animals; Lyme disease; wild animal workers